In Vitro Effect of Denture Cleansers on the Color Stability of Polyetheretherketone and Other Denture Base Polymers - Tekin, Samet (Univ Costa Rica, Fac Odontologia, 2022)
The aim of this in vitro study was to compare the long-term effect of overnight use of denture cleansers with different chemical compositions on the color stability of denture base polymers (DBPs). The four DBPs evaluated were PEEK (PK group), thermoinjection-molded polyamide (PA group), auto-polymerized polymethylmethacrylate (PMMA) (AP group), and heat-polymerized resin PMMA (HP group). The cleaning agents used were Corega tablet (CT), Protefix tablet (PT), and 0.5% sodium hypochlorite (NaOCl) solution (SH). Distilled water (DW) served as a control. Forty-eight disc-shaped specimens (10mm x 2mm) were prepared from each DBP and randomly immersed in the different storage media (n=12 in each group). Color measurements of the specimens before and after immersion in the denture cleansers were made using a spectrophotometer (VITA Easyshade V). The color changes were measured and recorded in L* a* b*. After 120 d, the CIEDE2000 formula was used to calculate color changes (Delta E00). For analysis of the data, a multivariate analysis of variance was used (p<0.05). The results of the statistical analysis revealed significant color change differences in the DBPs immersed in the various denture cleansers (p<0.05). Groups PA and PK showed the highest values for all solutions. AP-SH showed the highest Delta E00 value in group AP, no significant difference was found between other solutions. In group HP, there was no statistically significant difference between the average Delta E00 values of all solutions. Long-term daily use of the denture cleansers affected the color stability of all the DBPs, although the level of color change was acceptable. Laboratory and clinical studies on the color stability of PEEK are needed to confirm the results of this study.
Efecto in vitro de los limpiadores de prótesis en la estabilidad del color de la polieteretercetona y otros polímeros base de prótesis
Keywords: Color stability; Denture base material; PEEK; PMMA; Polymer